2015
DOI: 10.7461/jcen.2015.17.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic Carotid-Cavernous Fistula after Stent Assisted Coil Embolization of Posterior Communicating Artery Aneurysm

Abstract: Stent assisted coiling (SAC) is a useful technique for the treatment of wide necked complex aneurysm. As the frequency of SAC increases, stent-related complications such as thromboembolism, aneurysm rupture, and vessel rupture have been reported. However, to the best of our knowledge, carotid-cavernous fistula (CCF) after SAC has never been reported. The authors experienced a case of direct CCF after a SAC procedure for treatment of a complex posterior communicating artery (PCoA) aneurysm regrowth, which was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…On the other hand, the clinical course of iatrogenic CCF following endovascular intervention is often benign, even though being type A with high‐flow shunting . Park HR et al reported a case of iatrogenic CCF, created by the proximal tip of Solitaire stent after stent assisted coil embolization of posterior communicating artery aneurysm . The high‐flow shunt was still present 7 days post procedure, but remained asymptomatic 3 months later under conservative treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, the clinical course of iatrogenic CCF following endovascular intervention is often benign, even though being type A with high‐flow shunting . Park HR et al reported a case of iatrogenic CCF, created by the proximal tip of Solitaire stent after stent assisted coil embolization of posterior communicating artery aneurysm . The high‐flow shunt was still present 7 days post procedure, but remained asymptomatic 3 months later under conservative treatment.…”
Section: Discussionmentioning
confidence: 99%
“…None of the CCF resulted in clinical sequela, and all healed spontaneously at follow‐up angiography. Arterial wall injury in endovascular intervention is caused by vessel wall disruption from intima towards adventitia, unlike traumatic or iatrogenic CCF during trans‐sphenoidal surgery, in which the disruption is from adventitia towards intima and usually more extensive . As the CCF was detected before complete revascularization of the proximal carotid artery, the low in‐flow pressure limited the fistula flow and pressure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only 1 case of CCF during treatment with the Willis covered stent has been reported. 28 CCF was most likely due to arterial vascular lesion(s) caused by guiding catheter, guidewire, or balloon inflation during stent delivery into the tortuous PA.. 28,29 The skills of the doctors performing the procedure are important in minimizing vascular injuries associated with stent delivery.…”
Section: Other Complicationsmentioning
confidence: 99%